Konstruksi Kebenaran dalam Evidence-Based Policy Making: Analisis Wacana Kritis atas Kebijakan Penanggulangan Kemiskinan di Provinsi Banten - Supriatno, Eko; Pahdepie, Fahd; Salam, Rahmat; Andriansyah, Andriansyah (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
Evidence-Based Policy Making (EBPM) is often presented as a rational and objective policy ideal, yet evidence is not neutral; it is constructed through power relations, interests, and epistemic frameworks. Using Critical Discourse Analysis grounded in social constructivism and Michel Foucault’s theory of power, this study examines poverty alleviation policy in Provinsi Banten. The analysis draws on provincial planning documents (RPJMD/RPD and RKPD), Bappeda Provinsi Banten policy documents, and BPS poverty releases and press statements. Findings identify a recurring EBPM discourse that privileges macro indicators and performance metrics to narrate “progress,” while marginalizing intra-provincial inequality and contested definitions of “the poor.” Evidence therefore does not “speak for itself” but is mediated by values, policy paradigms, and dominant actors’ interests. The article argues for EBPM that integrates ethical and epistemological reflexivity and local context so policy is not only scientific but also fair and inclusive.